Pengembangan LKPD Pada Materi Teks Cerita Pendek Siswa SMA Katolik 2 Kabanjahe Berbantuan Aplikasi Quizizz - Pita Epriani Br Sinuraya; M. Oky Fardian Gafari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this research is to explain the process of development, produce the product, and explain the effectiveness of the learner's work sheet (LKPD) assisted by the application of quizizz in the short story text in the students of the X class of Private Catholic High School 2 Kabanjahe. This type of research is research and development (R&D) with research design ADDIE development model consists of 4 main stages: Analysis, Design, Develop, Implementation, and Evaluation. Data collection techniques are the lifts given to media experts, material experts, and pupils. The test subject is limited to students/I grade XI IPS 1 of 32 people. Data analysis techniques are quantitative descriptive of material experts, media experts and student respondents. The results of the validation of the expert of the material were 93.1, of the media expert was 96.73, and the student response was 91.98. The evaluation of LKPD's eligibility assessment of the application of quizizz on short story material for eleventh grade students by the experts of the materials, the media experts and the students obtained a total ratio of 93.92 who entered the category was very good. The result of this study was LKDP with the help of the quizizz application of short story materials for eleventennial students. Recommendations for further research are expected to develop LKPP by using other applications with broader and better material.